2016
DOI: 10.20944/preprints201611.0134.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<em>Ginkgo Biloba</em> for Reducing Hyperlipideamia: Case Study

Abstract: Hyperlipidemia case was described as a rise of lipid profile or lipoproteins in the blood. This study describe briefly investigate the reducing hyperlipideamia impact of Ginkgo biloba on the level of lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This result was agreed with (Caroline J. Smith et al) [20]who found a significant difference in iNOS levels in hypertensive patients. Albumin contains a free sulfhydryl group, this forms a disulfide with several compounds like cysteine, homocysteine, or glutathione, Albumin is able to scavenge hydroxyl radicals [21], the decrease in albumin in patient is agreed with results of (Oda E. et al2012)in Hypertension [15] who suggested that result is may be due to its function as antioxidant activity so the non-oxidized albumin is decrease in addition to negative acute phase protein, so inflammation is considered the principle cause of a decrease in the serum albumin [21].…”
Section: Resultssupporting
confidence: 92%
“…This result was agreed with (Caroline J. Smith et al) [20]who found a significant difference in iNOS levels in hypertensive patients. Albumin contains a free sulfhydryl group, this forms a disulfide with several compounds like cysteine, homocysteine, or glutathione, Albumin is able to scavenge hydroxyl radicals [21], the decrease in albumin in patient is agreed with results of (Oda E. et al2012)in Hypertension [15] who suggested that result is may be due to its function as antioxidant activity so the non-oxidized albumin is decrease in addition to negative acute phase protein, so inflammation is considered the principle cause of a decrease in the serum albumin [21].…”
Section: Resultssupporting
confidence: 92%
“…Even more, our previous observation of the marked improvement of dyslipidemic and high glucose status in diabetic rat,21 could be attributed to our current findings of the ameliorating effects of GB and MW on the pancreatic β-cells. Similarly, it was reported that GB reduced hyperlipidemia41 that has been suggested to be due to its content of flavonoid components 42. The MW has been also reported to have a powerful hypolipidemic action in T2D 43.…”
Section: Discussionmentioning
confidence: 79%